2022
DOI: 10.3389/fpsyg.2022.1073017
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on lifestyle and financial behaviour: The implications to research in financial vulnerability

Abstract: The outbreak of coronavirus pandemic in late 2019 posted unprecedented social-economic challenges and disruptions to societies and individuals. The “new-normal” styles of living and working could intertwined with other determinants complicating the investigation of individual’s financial vulnerability. The purpose of this paper is to conduct literature survey to review and consolidate the recent scattered literatures to identify some possible factors to be considered in the research related to financial vulner… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…In addition, we found that working-age adults with COVID had higher odds of stress due to inflation compared to those without COVID. Such findings could probably, in part, be explained as COVID may have affected financial vulnerability, changing some individuals' economic activities and their financial behaviors [31,32]. COVID affected more females and poor families, which happen to be more vulnerable to stress due to inflation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, we found that working-age adults with COVID had higher odds of stress due to inflation compared to those without COVID. Such findings could probably, in part, be explained as COVID may have affected financial vulnerability, changing some individuals' economic activities and their financial behaviors [31,32]. COVID affected more females and poor families, which happen to be more vulnerable to stress due to inflation [33].…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, we focus on the following four financial behaviours: earning, spending, investment and debt. The above newly identified factors are mapped onto the cause-effect chain of financial vulnerability of Van Aardt et al's model [16] as described in Ma et al [34].…”
Section: Variables For Change In Financial Behavioursmentioning
confidence: 99%
“…For example, in Germany, the number of people in short-time work increased drastically with the beginning of the pandemic (Bundesagentur für Arbeit, 2020). Overall, the financial situation of many people worsened during the course of the pandemic (Ma et al, 2022). Considering that the rate of unemployment in Germany in April 2020 increased by 18.6% compared to the previous year, this worry seems to be a comprehensible reaction (Bundesagentur für Arbeit, 2020).…”
Section: Covid-19-related Stressmentioning
confidence: 99%